Intergroup Contact and Housing Selection of United States Study Abroad Students - Frekot, Elizabeth (Department of Psychology, 2022)
Since its introduction by Allport (1954; Nature of Prejudice), the contact hypothesis has expanded beyond understanding the relationship between intergroup contact and prejudice reduction (Zuma, 2014). The contact hypothesis has also been used to understand the relationship between intergroup contact and intercultural attitudes and cross-group friendships (Tawagi & Mak, 2014). This research aimed to understand the impact of housing as a catalyst for intergroup contact as it relates to negative intercultural attitudes and intergroup anxiety for United States Semester Study Abroad students at the University of Cape Town (UCT). A longitudinal quasi-experimental design was used to examine the impact of housing type on factors of intergroup contact, like quantity and quality of contact with SA students, negative and positive contact, intergroup anxiety and negative intercultural attitudes, over the US study abroad semester and when they return home. Two surveys were administered while US students were in-country and one administered when they returned home. Mixed linear models and longitudinal path models were used to analyze relationships between the variables over time. The current study showed an impact of program housing on the quantity and quality of contact with SA students and negative intercultural attitudes over time. US study abroad students living in UCT Residence and Campus Key reported more quantity of contact with SA students, especially Black SA students. The housing type of the US student impacted negative intercultural attitudes and quality of contact, moderated by time. This research expands the growing literature about the impact of intercultural and international contact on longitudinal effects of study abroad. Future research could expand on the current research by exploring the kind of contact US students have with SA students based on housing and expand on the preliminary results on where intergroup contact occurs with White and Black SA students.